Damage Initiation Analysis of a Tension Stiffened Composite PRSEUS Panel Based on Modified Hashin Criteria - Yongjie Zhang; Samya Ettoumi; Bo Cui; Jingpiao Zhou (International Journal of Aerospace Engineering)
In this study, a damaged three-stringer PRSEUS panel simulating a midbay-to-midbay damage scenario was modelled in Abaqus and analyzed under tension. Moreover, employing the Abaqus built-in Hashin failure criteria verified the reliability of the criteria in predicting damage initiation with great accuracy. Further, these criteria were implemented via UMAT to investigate the effect of shear stress on the analysis, indicating that manipulating the coefficient of shear stress contribution led to a significant enhancement in analysis accuracy. Lastly, the same procedure was followed in the analysis of a repaired three-stringer panel, validating once again the adequacy of the adopted approach and simultaneously highlighting the efficiency of the repair technique in restoring load carrying of the PRSEUS panel. This study may provide a dependable reference presenting a simplified and significantly less computationally demanding approach for damage analysis composite structures and their repair, in addition to further applying these techniques to access the damage-arresting capabilities of these structures.